Digital Transformation and Management in the Industry 4.0 Era - Muhammad Faisal; Uray Andrey Indra Maulana; Rizki Fakhrul Yahya; Rina Mayasafitri; Muhammad Zalviwan (Civiliza Publishing, Indonesia., 2026)
The fourth industrial revolution is marked by the implementation of cyber-physical systems, the Internet of Things, big data analytics, and Artificial Intelligence which fundamentally changed the way organizations operate, make decisions, and manage human resources. The purpose of this study is to analyze the impact of digital transformation on management management on the dimensions of organizational structure, data-driven decision-making, human resource management, business process efficiency, and leadership. The method used was a systematic literature review of 20 international and national indexed journal references for the 2021–2026 period which were purposively selected. The results show that digital transformation is driving an organizational paradigm shift from hierarchical structures to collaborative networks, from intuitive to evidence-based decision-making, as well as from conventional HR management to digital HR with the integration of AI and big data analytics. The results of the NewVantage Partners report referenced by Berndtsson et al. (Berndtsson et al., 2023) show that only 19.3% of Fortune 1000 companies have successfully built a data-driven culture, while non-technical barriers account for 91.9% of the overall data-driven transformation challenges. The conclusions of the study show that the success of digital transformation in management management depends not only on the adoption of technology, but also on the readiness of the organization's culture, digital leadership, and the dynamic capabilities of human resources